Marka yönetiminde spor sponsorluğunun tercih kriterleri - Keskin, Tamer (My University, 2004)
Bu çalışmada, spor sponsorluğu tercih kriterleri, takım ve spor sponsorluğu olguları karşılaştırılarak incelenmiştir. Çalışmada kullanılan veriler, sponsorluk yapan markaların ve spor organizasyonu sahiplerinin yaptırmış olduğu araştırmalardan alınmış ikincil verilerdir.İncelenen her iki sponsorluk türünün, birbirine karşı olan üstünlükleri ve zayıflıkları saptanmıştır. Aslında iki sponsorluk türünün birbirinin rakibi olmadığı, beraber uygulandığı örneklerde de birbirinin tamamlayıcısı olduğu gözlenmiştir. Çalışmanın ortaya çıkan sonuçlarından biri; sponsorluk tercihi yaparken en önemli etkenin, marka ve ürünün karakteristik özellikleri ile sponsorluk yapılacak alan arasında uyum olması gereklililiğidir. Diğer önemli sonuç ise, doğru seçilmiş spor sponsorluğunun tek başına başarı için yeterli olmadığı ve doğru iletişim etkinlikleri ile sponsorluğun desteklenmesinin başarının belirleyicisi olduğudur. Spor sponsorluğunun başarısının sağlanması, sporun iletişim dilini doğru bir şekilde kullanarak ve pazarlama iletişimi araçlarından maksimum ölçüde faydalanarak, hedef kitleye etkin bir şekilde ulaşmakla gerçekleştirilebilir.

Name and Surname: Tamer Keskin Field: Business Administration Programme: Management and Organization Supervisor: Prof.Dr. İbrahim Anıl Degree Awarded and Date: Master - December 2004 Brand Management, Sponsorship, Sports Sponsorship, Sports Marketing, Marketing Communication. ABSTRACT PREFERENCE CRITERIA OF SPORTS SPONSORSHIP IN THE BRAND MANAGEMENT This study examines the preference criteria of sports sponsorship and the facts of team and sports sponsorship by comparison. The data used in this study are secondary data taken from the researches by the sponsoring brands and owners of sports organizations.The superiorities and weaknesses of each of the two examined sponsorship types over the other are determined. It is observed that, as a matter of fact, the two sponsorship types are not opponents, and they are even complementary to one another in the cases they are implemented together. One of the results of this study is that the most important factor in making a sponsorship preference is the compatibility between the characteristics of the brand/ product and the area to be sponsored. Another important result is that a sponsorship that is chosen appropriately is not enough for success on its own; it should also be supported by appropriate communication activities. The success of sports sponsorship is possible only if the target groups are effectively reached by using the communicational language of sports correctly and by exploiting the marketing communication tools at maximum.
Keywords: Marka Yönetimi; Sponsorluk